2008
DOI: 10.1093/brain/awn272
|View full text |Cite
|
Sign up to set email alerts
|

Influence of basal ganglia on upper limb locomotor synergies. Evidence from deep brain stimulation and L-DOPA treatment in Parkinson's disease

Abstract: Clinical evidence of impaired arm swing while walking in patients with Parkinson's disease suggests that basal ganglia and related systems play an important part in the control of upper limb locomotor automatism. To gain more information on this supraspinal influence, we measured arm and thigh kinematics during walking in 10 Parkinson's disease patients, under four conditions: (i) baseline (no treatment), (ii) therapeutic stimulation of the subthalamic nucleus (STN), (iii)L-DOPA medication and (iv) combined ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 84 publications
7
36
0
Order By: Relevance
“…The latter parameter was computed as the time delay between the positive peak of arm angle (maximum forward inclination) and the negative peak of the ipsilateral thigh angle (maximum backward inclination), identified between 20 and 80% of the stride cycle. When the upper limb produced two oscillations per stride at low walking speeds, point estimates of relative phase were computed using the first positive peak of arm oscillation and the negative peak of the ipsilateral thigh angle (Crenna et al 2008;Ford et al 2007).…”
Section: Data Processingmentioning
confidence: 99%
“…The latter parameter was computed as the time delay between the positive peak of arm angle (maximum forward inclination) and the negative peak of the ipsilateral thigh angle (maximum backward inclination), identified between 20 and 80% of the stride cycle. When the upper limb produced two oscillations per stride at low walking speeds, point estimates of relative phase were computed using the first positive peak of arm oscillation and the negative peak of the ipsilateral thigh angle (Crenna et al 2008;Ford et al 2007).…”
Section: Data Processingmentioning
confidence: 99%
“…Related research has highlighted upper-limb gait asymmetry and coordination deficits as a common and relatively early feature of PD [1012]. Biomechanically, several lines of evidence suggest that impaired arm swing may arise from wrongly timed activation of the shoulder flexors or extensors [13], axial rigidity [14, 15], and/or loss of trunk rotation during ambulation [1618]. The relationship between dopamine deficits and these upper-limb gait changes in PD, however, remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…First, using [ 123 I] N-ω-fluoropropyl-2β-carbomethoxy-3β-(4-iodophenyl)-tropane (FP-CIT) and single-photon computed tomography, Isaias et al [19] reported that asymmetric dopaminergic terminal labeling in the striatum correlates strongly with upper-limb gait asymmetry in PD subjects. Second, combined dopaminergic medication and bilateral subthalamic nucleus (STN) stimulation have been shown to ameliorate reduced walking arm swing amplitude among PD patients [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…While the current study was limited by sample size, our results are in agreement with previous characterizations of gait impairment in early PD. Specifically, several studies have suggested that gait impairment in early PD may involve reduced swing of the upper limbs during ambulation (Huang et al 2012; Lewek et al 2010; Isaias et al 2012; Crenna et al 2008; Carpinella et al 2007; Roggendorf et al 2012). Moreover, the agreement of our results with previous studies supports the notion that whole-body data mining techniques may be used to reveal novel markers of gait dysfunction.…”
Section: Pd Detection Studymentioning
confidence: 99%